Essential guide to perennial gardening : techniques and know-how for planning, planting, and tending low-maintenance perennial plantings (Cool Springs Press, 2025)
"From the foremost authority on gardening in North America comes the American Horticultural Society Essential Guide to Perennial Gardening, a comprehensive reference book about growing perennial plants"--